INCLUSIVE EDUCATION: STRATEGIES FOR ENHANCING PARTICIPATION AND ACHIEVEMENT OF STUDENTS WITH SPECIAL NEEDS - Reyaz Ahmad Bhat (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Abstract: This research paper investigates the significance of inclusive education in promoting the active participation and academic achievement of students with special needs. By examining scholarly literature, case studies, and practical approaches, the paper explores effective strategies that educational institutions can adopt to create inclusive environments, address challenges, and ensure optimal learning outcomes for all students.